The Role of Classical Test Theory to Determine the Quality of Classroom Teaching Test Items: Peran Teori Uji Klasik untuk Menentukan Kualitas Item Tes Pengajaran di Kelas - Vincent, Wong; Shanmugam, S.Kanageswari Suppiah (Universitas Muhammadiyah Sidoarjo, 2020)
The purpose of this study is to describe the use of Classical Test Theory (CTT) to investigate the quality of test items in measuring students' English competence. This study adopts a research method with a mixed methods approach. The results show that most items are within acceptable range of both indexes, with the exception of items in synonyms. Items that focus on vocabulary are more challenging. What is surprising is that the short answer items have an excellent item difficulty level and item discrimination index. General results from data analysis of items also support the hypothesis that items that have an ideal item difficulty value between 0.4 and 0.6 will have the same ideal item discrimination value. This paper reports part of a larger study on the quality of individual test items and overall tests.